c-erbB-2 expression and nuclear pleomorphism in canine mammary tumors - Dutra,A.P. (2004)
The objective of the present investigation was to study the expression of c-erbB-2 and MIB-1 and try to associate them with morphological features of the cell such as nuclear pleomorphism, mitotic count and histological grade in a series of 70 canine mammary gland tumors, 22 of them benign and 48 malignant. Tumors were collected at the Veterinary Hospital of UFMG (Brazil) and the Veterinary Faculty of Porto University (Portugal). c-erbB-2 expression was determined according to the guidelines provided by the manufacturer of the HercepTest system and nuclear pleomorphism, mitotic count and histological grade according the Elston and Ellis grading system. The HercepTest is the FDA-approved in vitro diagnostic test marketed by Dako. It is a semi-quantitative immunohistochemical assay used to determine overexpression of HER2 protein (human epidermal growth factor receptor) in breast cancer tissue. MIB-1 expression was also evaluated in 28 malignant tumors. Seventeen (35.4%) of the malignant tumors were positive for c-erbB-2 expression, which was positively associated with nuclear pleomorphism (P < 0.0001), histological grade (P = 0.0017) and mitotic count (P < 0.05). Nuclear pleomorphism also showed a positive association with MIB-1 index (P < 0.0001). These results suggest that some of the biological and morphological characteristics of the tumor are associated in canine mammary gland tumors, as also reported for human breast cancer. It was also possible to show that the immunoexpression of c-erbB-2 can be a factor in mammary carcinogenesis. This fact opens the possibility of using anti-c-erbB-2 antibodies in the treatment of canine mammary tumors.